INTEGRASINILAI-NILAI PENDIDIKANaL QURAN DAN BUDAYA DALAM TRADISI MAULID FATIMAH DI KAMPUNG CIKAMPEK KOTA SERANG - Nanda Agustina; Putri Mamduhah Handayani; Ina Salma Febriani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Antasari Banjarmasin, 2025)
Abstact: Â Every year, precisely in the month of Rabiul Awwal, Muslims around the world usually commemorate the birth or birthday of the Prophet Muhammad SAW with great joy. However, the people of Banten not only perform the ritual of the birthday of the Prophet Muhammad SAW, but also the